IN VITRO ACTIVITY OF VACCINIUM MACROCARPON (CRANBERRY) ON URINARY TRACT PATHOGENS IN UNCOMPLICATED URINARY TRACT INFECTION - Bukhari, Saima; Chiragh, Sadia; Tariq, Sumbal; Alam, Muhammad Adeel; Wazir, Muhammad Salim; Suleman, Muhammad (Journal of Ayub Medical College Abbottabad, 2015)
Background: Urinary tract infection is the most common bacterial infection in the community, mainly caused by Escherichia coli (E coli). Due to its high incidence and recurrence, problems are faced in the treatment with antibiotics. Cranberry being herbal remedy have long been the focus of interest for their beneficial effects in preventing urinary tract infections. This study was conducted to analyse in vitro activity of cranberry (Vaccinium macrocarpon) on uropathogenic E coli in uncomplicated urinary tract infections. Methods: In this laboratory based single group experimental study, anti-bacterial activity of Vaccinium macrocarpon concentrate on urinary tract E coli was investigated, in vitro. Ninety-six culture positive cases of different uropathogens were identified. Vaccinium macrocarpon concentrate at different concentrations was prepared in distilled water and put in wells punched in nutrient agar. E coli isolates were inoculated on the plates and incubated at 37 oC for 24 hours. A citric acid solution of the same pH as that of Vaccinium macrocarpon was used and put in a well on the same plate to exclude the effect of pH. Results: A total of 35 isolates of E coli were identified out of 96 culture positive specimens of urine and found sensitive to Vaccinium macrocarpon (p< 0.000). Results revealed that Vaccinium macrocarpon has antibacterial effect against E coli. Furthermore the antibacterial activity of Vaccinium macrocarpon has dose response relationship. Acidic nature of Vaccinium macrocarpon due to its pH is not contributory towards its antibacterial effect. Conclusion: Vaccinium macrocarpon concentrate may be used in urinary tract infection caused by E coli.